PESANTREN SEBAGAI MATA AIR KEBUDAYAAN - Zastrouw, Ngatawi el (The International Journal of Pegon : Islam Nusantara civilization, 2018)
Besides as a center of education that teaches and spreads Islam, pesantren is actually the center of Islamic culture of Nusantara.Walisongo is the foundation of a cultural strategy that makes traditions and cultural arts as means or instruments (wasilah) and methods(manhaj) in teaching and spreading Islam in Nusantara. Walisongo’s cultural strategy is continued by pesantren in the next phase, especiallywhen facing Western culture in the colonial era. since then the pesantren became the springs of culture that inspired the ulama and ummaatIslam Nusantara when in touch and dealing with the various cultures that came later, especially secular modern culture with the ideologicaltools that accompany it.